Anion-dependent dysprosium() cluster single-molecule magnets - Liu, Cai-Ming; Hao, Xiang (New journal of chemistry, 2023)
A new Schiff base ligand, which is formed by the condensation reaction of 5-fluorosalicylaldehyde and pyrimidine-4-carbonyl hydrazide {H 2 L Schiff = ( E )- N ′-(5-fluoro-2-hydroxybenzylidene)pyrimidine-4-carbohydrazide}, was made to react with different dysprosium( iii ) salts in an alkaline solution to assemble Dy 4 and Dy 6 cluster complexes, [Dy 4 (OH) 2 (L Schiff ) 4 (H 2 O) 2 (NO 3 ) 2 ]·4MeCN·MeOH ( 1 ) and [Dy 6 (CO 3 ) 2 (L Schiff ) 6 (H 2 O) 3 (MeOH)Cl 2 ]·5MeOH ( 2 ), depending on whether the anion used is nitrate or chloride. Complex 1 corresponding to the nitrate anion is a butterfly-like Dy 4 cluster complex with four different Dy( iii ) coordination configurations of [O 6 N 2 ], [O 8 N], [O 7 N 2 ] and [O 6 N 3 ]; when the anion is replaced by the chloride anion, carbon dioxide can be automatically captured from the air and converted into a carbonate bridging ligand, and the final product obtained is complex 2 , which is a triangular prism-type Dy 6 cluster complex with double μ 3 -carbonate bridging ligands. Both 1 and 2 show good zero-field SMM properties, with U eff / k values of 116.5 K for 1 and 150.9 K for 2 . The same Schiff base ligand was used to assemble different zero-field Dy( iii ) cluster single-molecule magnets with a nuclei number of 4 or 6, depending on the anions.